Primary Angiosarcoma of the Gastrointestinal Tract: A Systematic Review of the Literature - Dimitrios Schizas; Aikaterini Mastoraki; Ilias Giannakodimos; Alexios Giannakodimos; Afroditi Ziogou; Ioannis Katsaros; Maximos Frountzas; Ioannis Koutelidakis; Pantelis Vassiliu; Emmanouil Pikoulis (Journal of Investigative Surgery, 2022)
Primary Gastrointestinal Angiosarcoma (PGAS) constitutes a rare malignant tumor arising from vascular or lymphatic endothelial cells. The aim of this study was to review the available literature on PGAS and to elucidate its biological behavior and optimal therapeutic approach. PubMed and Embase bibliographical databases were systematically searched (last search April 8th, 2020) for studies concerning PGAS. Ninety-eight studies met our inclusion criteria, involving 110 patients (male/female = 1.5) with an age of 62.40 ± 17.84 (mean, SD) years. They were most frequently located at small (44.5%) and large intestine (35.5%), while 12.7% were multifocal. Surgical resection of the tumor was conducted at 84.0% of the cases combined with adjuvant therapy at 12.3%. One-year cumulative survival was 55.18% (95% CI: 34.33%–71.84%) for large intestine, 30.2% (95% CI: 17.1%–44.5%) for small intestine, whereas multifocal PGAS had a 6-months cumulative survival of 23.08% (95% CI: 5.58%–47.46%). Therefore, PGAS is an extremely rare entity with atypical clinical presentation, challenging diagnosis and aggressive behavior. High clinical suspicion is crucial for its prompt management. Further studies and the development of novel therapeutic agents are required in order to improve survival.